From Pathogenesis, Clinical Manifestation, and Diagnosis to Treatment: An Overview on Autoimmune Pancreatitis - Ou Cai; Shiyun Tan (Gastroenterology Research and Practice)
Autoimmune pancreatitis (AIP) is a special type of chronic pancreatitis which is autoimmune mediated. The international consensus diagnostic criteria (ICDC) 2011 proposed two types of AIP: type I is associated with histological pattern of lymphoplasmacytic sclerosing pancreatitis (LPSP), characterized by serum IgG4 elevation, whereas type 2 is named idiopathic duct-centric pancreatitis (IDCP), with granulocytic epithelial lesion (GEL) and immunoglobulin G4 (IgG4) negative. The pathogenic mechanism is unclear now; based on genetic factors, disease specific or related antigens, innate and adaptive immunity may be involved. The most common clinical manifestations of AIP are obstructive jaundice and upper abdominal pain. The diagnosis can be made by a combination of parenchymal and ductal imaging, serum IgG4 concentrations, pancreatic histology, extrapancreatic disease, and glucocorticoid responsiveness according to ICDC 2011. Because of the clinical and imaging similarities with pancreatic cancer, general work-up should be done carefully to exclude pancreatic malignant tumor before empirical trial of glucocorticoid treatment. Glucocorticoid is the most common drug for AIP to induce remission, while there still exists controversy on steroid maintenance and treatment for relapse. Further studies should be done to identify more specific serum biomarkers for AIP, the pathogenic mechanisms, and the treatment for relapse.